WISDOM project – VII. Molecular gas measurement of the supermassive black hole mass in the elliptical galaxy NGC 7052 - Smith, MD; Bureau, M; Davis, TA; Cappellari, M; Liu, L; Onishi, K; Iguchi, S; North, EV; Sarzi, M; Williams, TG (Oxford University Press, 2021)
Supermassive black hole (SMBH) masses can be measured by resolving the dynamical influences of the SMBHs on tracers of the central potentials. Modern long-baseline interferometers have enabled the use of molecular gas as such a tracer. We present here Atacama Large Millimeter/submillimeter Array observations of the elliptical galaxy NGC 7052 at 0′′.11 (⁠37pc) resolution in the 12CO(2-1) line and 1.3 mm continuum emission. This resolution is sufficient to resolve the region in which the potential is dominated by the SMBH. We forward model these observations, using a multi-Gaussian expansion of a Hubble Space Telescope F814W image and a spatially constant mass-to-light ratio to model the stellar mass distribution. We infer an SMBH mass of 2.5±0.3×109M⊙ and a stellar I-band mass-to-light ratio of 4.6±0.2M⊙/L⊙,I (3σ confidence intervals). This SMBH mass is significantly larger than that derived using ionized gas kinematics, which however appears significantly more kinematically disturbed than the molecular gas. We also show that a central molecular gas deficit is likely to be the result of tidal disruption of molecular gas clouds due to the strong gradient in the central gravitational potential.